Sea urchin response to rising pCO2 shows ocean acidification may fundamentally alter the chemistry of marine skeletons - BRAY, L.; PANCUCCI-PAPADOPOULOU, M.A.; HALL-SPENCER, J. M. (Hellenic Centre for Marine Research, 2014)
Ocean acidification caused by an increase in pCO2 is expected to drastically affect marine ecosystem composition, yet there is much uncertainty about the mechanisms through which ecosystems may be affected. Here we studied sea urchins that are common and important grazers in the Mediterranean (Paracentrotus lividus and Arbacia lixula). Our study included a natural CO2 seep plus reference sites in the Aegean Sea off Greece. The distribution of A. lixula was unaffected by the low pH environment, whereas densities of P. lividus were much reduced. There was skeletal degradation in both species living in acidified waters compared to reference sites and remarkable increases in skeletal manganese levels (P. lividus had a 541% increase, A. lixula a 243% increase), presumably due to changes in mineral crystalline structure. Levels of strontium and zinc were also altered. It is not yet known whether such dramatic changes in skeletal chemistry will affect coastal systems but our study reveals a mechanism that may alter inter-species interactions.